Erzeugen Religionen Gewalt? Eine Lesehilfe für religiöse Konflikte in modernen Gesellschaften - Reis, Oliver (Verschiedenheit als Diskurs)

Kirche und Geld: Nutzung oder Unterwerfung unter die Macht des Geldes? - Reis, Oliver (Hirschberg)

Promovieren zwischen Anpassung und Eigenständigkeit: Promotionscoaching als Begleitung eines komplexen Leistungsprozesses - Carell, Angela; Reis, Oliver; Szczyrba, Birgit (Forschung und Förderung. Promovierende im Blick der Hochschule)

Beraten und Beratenwerden in der Doktorandenbetreuung. Rollengestützte Forschung und Weiterbildung zur wissenschaftlichen Nachwuchsförderung - Reis, Oliver; Szczyrba, Birgit (Zeitschrift für Psychodrama und Soziometrie)

Religion lernen. Jahrbuch für konstruktivistische Religionsdidaktik

Didaktik eines Systematisch-theologischen Themas: Anthropologie für das Berufskolleg - Reis, Oliver (Kompetenzorientierte Lehre in der Theologie. Konkretionen – Reflexionen – Perspektiven)

Food intake of European adolescents in the light of different food-based dietary guidelines: results of the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study - Diethelm, Katharina; Jankovic, Nicole; Moreno, Luis A; Huybrechts, Inge; De Henauw, Stefaan; De Vriendt, Tineke; González-Gross, Marcela; Leclercq, Catherine; Gottrand, Frédéric; Gilbert, Chantal C; Dallongeville, Jean; Cuenca-Garcia, Magdalena; et al. (Public Health Nutrition)
Abstract Objective Since inadequate food consumption patterns during adolescence are not only linked with the occurrence of obesity in youth but also with the subsequent risk of developing diseases in adulthood, the establishment and maintenance of a healthy diet early in life is of great public health importance. Therefore, the aim of the present study was to describe and evaluate the food consumption of a well-characterized sample of European adolescents against food-based dietary guidelines for the first time. Design The HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study is a cross-sectional study, whose main objective was to obtain comparable data on a variety of nutritional and health-related parameters in adolescents aged 12·5–17·5 years. Setting Ten cities in Europe. Subjects The initial sample consisted of more than 3000 European adolescents. Among these, 1593 adolescents (54 % female) had sufficient and plausible dietary data on energy and food intakes from two 24 h recalls using the HELENA-DIAT software. Results Food intake of adolescents in Europe is not optimal compared with the two food-based dietary guidelines, Optimized Mixed Diet and Food Guide Pyramid, examined in this study. Adolescents eat half of the recommended amount of fruit and vegetables and less than two-thirds of the recommended amount of milk (and milk products), but consume much more meat (and meat products), fats and sweets than recommended. However, median total energy intake may be estimated to be nearly in line with the recommendations. Conclusion The results urge the need to improve the dietary habits of adolescents in order to maintain health in later life.

Sound & Image. An experimental study on the influence of acoustical parameters on the perception of a product’s image in TV-commercials - Flath, Beate (Audio Branding Year Book 2010)

"(...): dein einziges, dein höchstes Ziel ist gesunken -" oder: Ist es notwendig, mit der musikalisch-pädagogischen Praxis die Theoriebrille zu wechseln?. - Klingmann, Heinrich (Musizieren mit Schulklassen - Praxis, Konzepte, Perspektiven. Diskussion Musikpädagogik.)

„Ja also, das war ne gute Stunde“. Qualitätsmerkmale von Geschichtsunterricht aus Schülerperspektiven - Meyer-Hamme, Johannes (Geschichte in Wissenschaft und Unterricht 62 (2011) 5/6)

Complexity of numerical integration over spherical caps in a Sobolev space setting - Hesse, Kerstin (Journal of Complexity)

Theological Education Underground: 1937-1939

Kölving, Ulla und Courcelle, Olivier, Émilie Du Châtelet: Éclairages & documents nouveaux (Ferney Voltaire: Centre international d’étude du XVIIIe siècle) - Coelho Rodrigues, Ana Paula (Das achtzehnte Jahrhundert)

Philosophinnen oder Prinzessinnen? Anne Conway, Margaret Cavendish und die Neubewertung philosophierender Aristokratinnen des 17. und 18. Jahrhunderts - Hutton, Sarah (Von Diana zu Minerva. Philosophierende Aristokratinnen des 17. und 18. Jahrhunderts und ihre Netzwerke)

Emilie du Châtelet, Julien Offray de La Mettrie und Pierre Louis Moreau de Maupertuis im Zwiegespräch über das Glück - Coelho Rodrigues, Ana Paula (Von Diana zu Minerva. Philosophierende Aristokratinnen des 17. und 18. Jahrhunderts und ihre Netzwerke)

Emilie du Châtelet – Vom glücklichen Leben zur Freiheit des Denkens - Coelho Rodrigues, Ana Paula (Von Diana zu Minerva. Philosophierende Aristokratinnen des 17. und 18. Jahrhunderts und ihre Netzwerke)

Sport in der Schwangerschaft: bewegt gesund bleiben in NRW! ; Praxishilfe Sport bewegt NRW! - Satzinger, Nicole; Gellhaus, Ines

David Hilbert’s Lectures on the Foundations of Physics 1915–1927. Relativity, Quantum Theory and Epistemology, hg. v. Tilman Sauer und Ulrich Majer, in Zusammenarbeit mit Arne Schirrmacher und Heinz-Jürgen Schmidt, Springer: Berlin/Heidelberg 2009 (David Hilbert’s Lectures on the Foundations of Mathematics and Physics, 1891–1933; 5) - Peckhaus, Volker (Mathematical Reviews, MR2569313 (2011c:01023))

Frege, Gottlob, Grundgesetze der Arithmetik. Begriffsschriftlich abgeleitet. Band I und II. In moderne Formelnotation transkribiert und mit einem ausführlichen Sachregister versehen von Thomas Müller, Bernhard Schröder und Rainer Stuhlmann-Laeisz, Mentis: Paderborn 2009 - Peckhaus, Volker (zbMATH Open, Zbl. 1207.01040)

Frege, Gottlob, Grundgesetze der Arithmetik. Begriffsschriftlich abgeleitet. Band I und II. In moderne Formelnotation transkribiert und mit einem ausführlichen Sachregister versehen von Thomas Müller, Bernhard Schröder und Rainer Stuhlmann-Laeisz, Mentis: Paderborn 2009 - Peckhaus, Volker (Mathematical Reviews, MR2640900 (2011g:01017))